ANALISIS NOVEL AYAH KARYA ANDREA HIRATA DENGAN PENDEKATAN UNSUR INTRINSIK - Desty Endrawati Subroto; Danti Rahmawati; Dian Handayani; Yuliyawati Yuliyawati (LANGUAGE : Jurnal Inovasi Pendidikan Bahasa dan Sastra, 2026)
ABSTRACT Andrea Hirata's Ayah is not only a novel portraying a father's unconditional love but also a literary work constructed through the harmonious integration of intrinsic elements that shape its narrative quality. Although the novel has gained wide recognition among readers, comprehensive studies focusing on the interrelationship of its intrinsic elements remain limited. Therefore, this study aims to describe the intrinsic elements found in Andrea Hirata's Ayah. This research employed a descriptive qualitative method, with observation and note-taking techniques used to collect textual data. The data were analyzed through identification, classification, and interpretation of the novel's intrinsic elements, including theme, characterization, plot, setting, point of view, language style, and message. The findings indicate that the novel is dominated by the theme of paternal love and sacrifice, supported by well-developed characters, a mixed plot, settings in Belitung, Sumatra, and Australia, a third-person point of view, and language styles consisting of personification, metaphor, hyperbole, and Belitung Malay diction. These intrinsic elements are closely interconnected and function cohesively to construct a unified narrative, strengthen the novel's meaning, and enhance its literary and aesthetic value. ABSTRAK Novel Ayah karya Andrea Hirata tidak hanya mengangkat kisah kasih sayang seorang ayah, tetapi juga menyajikan struktur cerita yang kompleks melalui keterpaduan tema, tokoh, alur, latar, sudut pandang, gaya bahasa, dan amanat. Meskipun novel ini telah banyak mendapat apresiasi, kajian yang mendeskripsikan unsur-unsur intrinsiknya secara menyeluruh masih relatif terbatas. Oleh karena itu, penelitian ini bertujuan mendeskripsikan unsur-unsur intrinsik yang terdapat dalam novel Ayah karya Andrea Hirata. Penelitian menggunakan metode deskriptif kualitatif dengan teknik simak dan catat sebagai teknik pengumpulan data, sedangkan data dianalisis melalui identifikasi, klasifikasi, dan interpretasi terhadap unsur intrinsik novel. Hasil penelitian menunjukkan bahwa novel ini memiliki tema dominan tentang kasih sayang dan pengorbanan seorang ayah yang didukung oleh penokohan yang kuat, penggunaan alur campuran, latar Belitung, Sumatra, dan Australia, sudut pandang orang ketiga, serta gaya bahasa berupa majas personifikasi, metafora, hiperbola, dan diksi Melayu Belitung. Keseluruhan unsur intrinsik tersebut saling berkaitan secara harmonis sehingga membangun cerita yang utuh, memperkuat makna, nilai estetika, serta kualitas naratif novel Ayah karya Andrea Hirata.